DEVELOPMENT OF AN OPTICAL STRAIN MEASUREMENT METHOD - KHOO , KHOO SZE WEI (2011)
Strain measurement is important in mechanical testing. There are many strain measurement methods; namely electrical resistance strain gauge, extensometer, Geometric Moiré technique, optical strain measurement method and etc. Each method has its own advantages and disadvantages. There is always a need to develop a precise and yet simple strain measurement method in mechanical testing. The objective of this study is to develop a two-dimensional measurement algorithm that calculates the strain in a loaded structural component. This can be achieved by using the Digital Image Correlation technique which compares the displacement of the random speckles pattern in the reference (undeformed) and the deformed images. In the development of the strain measurement algorithm, it was coded into MATLAB program by using the MATLAB’s Image Processing Toolbox. Next, the tensile tests were conducted where two types of samples made of mild steel and polypropylene materials were tested using the Universal Testing Machine. Simultaneously, videos were recorded using a consumer version of high-definition video camera. The recorded videos (images) were then analyzed and the strain values were determined by using the optical strain measurement method (MATLAB program). In the results and discussions section, the stress-strain curves were plotted for the mild steel and the polypropylene specimens. From the stress-strain curves, the modulus of elasticity of the respective materials was determined and the results determined by the extensometer and the optical strain measurement method were compared to each other. The obtained results had been verified as the modulus of elasticity of the mild steel and the polypropylene specimens were found to be 5.14% and 2.35% off the benchmark values respectively. A good agreement was achieved upon comparison between the results determined by the two methods mentioned above. In conclusion, the two-dimensional deformation measurement algorithm had been successfully developed.